Research hotspots and trends on neuromyelitis optica spectrum disorders: insights from bibliometric analysis - Chen, Xin; Xiao, Jun; Zhou, Luo-Qi; Yu, Wen-Xiang; Chen, Man; Chu, Yun-Hui; Shang, Ke; Deng, Gang; Song, Wen-Hui; Qin, Chuan; Pan, Deng-Ji; Tian, Dai-Shi (Frontiers in Immunology, 2023)
Neuromyelitis optica spectrum disorders (NMOSD) are demyelinating diseases of the central nervous system, which aroused the great attention of researchers due to the relapsing courses and cumulative disability. The first bibliometric analysis of NMOSD was conducted to identify the research hotspots and emerging trends. Relevant articles published on NMOSD in the core collection of Web of Science were retrieved and analyzed through visualized analysis using CiteSpace and VOSviewer, focusing on annual publication trends, countries, institutions, authors, journals, and keywords. The analysis showed that over the past 30 years, publications related to NMOSD have shown steady growth with slight fluctuations. The United States played an important part in this field with the highest outputs and the greatest number of citations. Research hotspots of NMOSD have gradually shifted from the definition, biomarkers, and diagnostic criteria to diagnosis and treatment, particularly immunotherapy. This bibliometric analysis provides researchers with a theoretical basis for studying NMOSD and offers guidance for future research directions.